Anthropological Aesthetics of Greek Antiquity as a Narrative of Philosophical Discourse - Goncharova, O. M (Anthropological Measurements of Philosophical Research, 2022)
Purpose. The article aims to define the philosophical narratives about the "beautiful human" of Greek antiquity in the coordinates of the triad of "natural", "social" and "cultural" body. Theoretical basis. When achieving this purpose, the author based on the conceptual provisions of the philosophical anthropology of Н. Plessner, in particular, concerning the attitude of a limited body to its limit as an empirical comprehension of a human him/herself and the world. Developing the position of the body as a socio-cultural phenomenon and proceeding from the definition of corporeality as a "transformed human body under the influence of social and cultural factors, which has socio-cultural meanings and performs certain socio-cultural functions" (I. Bykhovskaya) (transl. by O. G.), the triad of "natural", "social" and "cultural" body was used as a methodological basis to analyse the research object. Originality lies in the explication of the peculiarities of aesthetic and anthropological discourse in Ancient Greek philosophy, not only through the prism of the dichotomy of "soul" and "body", but also through the prism of the triad "natural", "social" and "cultural" body, allowing rethinking of the narratives concerning the "beautiful human" of the formation period of the European anthropological aesthetics in Antiquity. Conclusions. The anthropological aesthetics of Greek Antiquity is masculine aesthetics, the aesthetics of the male "cultural body". If a man is an epistemological subject, he is able, despite the ugliness and abomination of his natural body, to reach the level of the cultural body, the level of "personal existence of corporeality". As for the female corporeality, since the Ancient Greek philosophy does not provide the status of an epistemological subject for a woman, she remains at the level of "social body".